Determinants of Corporate Sustainability Disclosure: The Case of the S&P/EGX ESG Index - Mohamed Gamal Elafify (Universitas Pasundan, 2021)
The paper investigates the influence of the corporate board and the dissemination of a separate sustainability report on the corporate sustainability disclosure (CSD) level of corporations listed on the Egyptian sustainability index from 2016–2018. This study used the score-weighting scheme assigned by the Egyptian Stock Exchange (EGX) to evaluate, list, and rank companies in terms of their CSD. Empirical results reveal that boards with higher independence and larger size generate a higher CSD score. The results also support the assumption that the issuance of a separate sustainability report boosts the CSD score. The current study provides insights for policymakers and regulators in developing countries, in general, and in Egypt, in particular, regarding the role of corporate board and issuance of a separate sustainability report in promoting CSD. To the best of the researcher’s knowledge, no prior study has discussed the determinants of the level of CSD for corporations listed on the sustainability index in Egypt.